The Biological Aspects Comparison of Nila Tilapia (Oreochromis Niloticus) on The Eutrophic and Oligotrophic Reservoir from Indonesia - Arfiati, Diana; Saputri, Nadya Agustarina; Styaningrum, Nimas; Widyastami, Asthervina; Dina, Karina Farkha; Lailiyah, Shofiyatul; Pratiwi, Rizky Kusma; Inayah, Zakiyyah Nur (Research Journal of Life Science, 2021)
Comparison of the length, weight and condition factor of Nila Tilapia (Oreochromis niloticus) was studied on oligotrophic waters (Wonorejo Reservoir) conducted from July to August 2018 and eutrophic waters (Selorejo Reservoir) on February to March 2019. All of the reservoir are in the East Java, Indonesia. The total sample from Wonorejo Reservoir about 79 fish from 3 times sampling (every two weeks), but the fish Sample from Selorejo Reservoir are 35 from 4 times sampling every week. The Nila Tilapia from Wonorejo Reservoir are 15.3 ± 2.5 cm (length) and 74.6 ± 38.6 grams (weight) but fish from Selorejo are 17.8 ± 2.2 cm average length and 114 ± 35 grams for the weight. The condition factor of Nila Tilapia in both reservoirs was relatively the same, with an average value was 1.01. The Nila Tilapia caught from Selorejo Reservoir (eutrophic) is relatively heavier and bigger than in the Wonorejo Reservoir (oligotrophic) even though the hook size is smaller. Fish from the Selorejo Reservoir (eutrophic) is easier to get food so that the average fish is larger.